PERBANDINGAN MODEL PEMBELAJARAN MAKE A MATCH DENGAN TALKING STICK PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS III SDN SIRNA JAYA - Sidik, Egi Mohamad; Permana, Rahmat; Taufik Saleh, Yopa (STKIP Subang, 2020)
In the learning process, especially in mathematics in third grade students at SDN Sirna Jaya, it is known that they still lack understanding of fraction material, learning centered on lecture methods, which causes students to feel bored and uninterested in the material. Based on the results of the Pre-test there are still some that have not reached the Minimum Criteria for completeness set by the school for mathematics subjects with a weight of 70. The purpose of this study is to find out Make A Match learning, Talking Stick learning and know the comparison of learning models Make A Match and Talking Stick learning model in mathematics subject matter in fractional grade III at SDN Sirna Jaya. This research is a quantitative study while the research method is an experimental research. The results showed that there was a comparison of the Make A Macth learning model with the Talking Stick with the acquisition of a significance result of 0.023 <0.05 so that the conclusion H0 was rejected and H1 accepted.